2018
DOI: 10.1063/1.5024408
|View full text |Cite
|
Sign up to set email alerts
|

Double photoionization of propylene oxide: A coincidence study of the ejection of a pair of valence-shell electrons

Abstract: Propylene oxide, a favorite target of experimental and theoretical studies of circular dichroism, was recently discovered in interstellar space, further amplifying the attention to its role in the current debate on protobiological homochirality. In the present work, a photoelectron-photoion-photoion coincidence technique, using an ion-imaging detector and tunable synchrotron radiation in the 18.0-37.0 eV energy range, permits us (i) to observe six double ionization fragmentation channels, their relative yields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…By this technique, we were able to produce and characterize several molecular dications such a CO 2 2+ [ 77 , 78 ], N 2 O 2+ [ 79 , 80 ], C 6 H 6 2+ [ 81 , 82 ], and C 2 H 2 2+ [ 83 , 84 ], and more recently C 3 H 6 O 2+ [ 85 , 86 ], C 2 H 5 NO 2+ [ 87 ] (the dications of methyloxirane and N-methylformamide, respectively), pointing out their important role in the upper atmosphere of planets of the Solar system. In all cases, we performed double photoionization experiments using the tunable linearly polarized synchrotron radiation (with photon energy resolution of about 1.5 meV) as it is available at the GasPhase and CiPo beamlines of Elettra measuring: (i) the threshold energy for the different open fragmentation channels; (ii) the relative cross sections; (iii) the KER distribution of fragment ions at different photon energies; (iv) the angular distributions of fragment final ions with the relative anisotropy parameter β [ 75 , 76 ].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…By this technique, we were able to produce and characterize several molecular dications such a CO 2 2+ [ 77 , 78 ], N 2 O 2+ [ 79 , 80 ], C 6 H 6 2+ [ 81 , 82 ], and C 2 H 2 2+ [ 83 , 84 ], and more recently C 3 H 6 O 2+ [ 85 , 86 ], C 2 H 5 NO 2+ [ 87 ] (the dications of methyloxirane and N-methylformamide, respectively), pointing out their important role in the upper atmosphere of planets of the Solar system. In all cases, we performed double photoionization experiments using the tunable linearly polarized synchrotron radiation (with photon energy resolution of about 1.5 meV) as it is available at the GasPhase and CiPo beamlines of Elettra measuring: (i) the threshold energy for the different open fragmentation channels; (ii) the relative cross sections; (iii) the KER distribution of fragment ions at different photon energies; (iv) the angular distributions of fragment final ions with the relative anisotropy parameter β [ 75 , 76 ].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Nowadays, and already for several decades, a wide number of experiments are carried out world-wide using circularly polarized tunable light sources of high intensity as synchrotron radiation and, in order to detect chirality in molecules, imaging photoelectron circular dichroism (Turchini et al, 2004; Stranges et al, 2005; Piancastelli et al, 2007; Alberti et al, 2008; Janssen and Powis, 2014). Moreover, techniques of molecular alignment with the pioneering work done by Zare et al (Sinha et al, 1974; Caldwell and Zare, 1977) and by B. Friedrich and D. R. Herschbach (Friedrich and Herschbach, 1991; Friedrich et al, 1991) have been found of great relevance to control the stereodynamics of elementary chemical processes occurring in the gas phase and at surfaces, and are arguably crucial in chirality issues (Falcinelli et al, 2018a). In particular, previous studies (Caldwell and Zare, 1977; Karny et al, 1978; Sanders and Anderson, 1984; Pullman et al, 1990; Aquilanti et al, 1994) indicate that molecular directionality and alignment should strongly amplify dichroism and provide stereodynamical mechanisms for discrimination of enantiomers, other than via circularly polarized light (Herwig et al, 2013; Pitzer et al, 2013; Tia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous studies (Caldwell and Zare, 1977; Karny et al, 1978; Sanders and Anderson, 1984; Pullman et al, 1990; Aquilanti et al, 1994) indicate that molecular directionality and alignment should strongly amplify dichroism and provide stereodynamical mechanisms for discrimination of enantiomers, other than via circularly polarized light (Herwig et al, 2013; Pitzer et al, 2013; Tia et al, 2017). Very recently, in our laboratory we are working, to couple a mechanical molecular velocity selector, specifically constructed ad hoc (able to control the velocity dependence of the molecular alignment) with a PEPIPICO (photo-electron-photo-ion-photo-ion coincidence) imaging device, in order to be used with a synchrotron radiation (Falcinelli et al, 2018a), delivering tunable intense photon sources with high degree of both linearly and circularly polarized light of both helicities. Double photoionization studies on propylene oxide enantiomeric molecules have been done by exploiting Auger spectroscopy (Piancastelli et al, 2007; Alberti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations